1991
DOI: 10.1007/bf01253386
|View full text |Cite
|
Sign up to set email alerts
|

Molecular structure and dynamics of acetylcholine

Abstract: Molecular dynamics simulations and energy calculations based on the AMBER force field were used to examine the molecular movements and low-energy conformations of acetylcholine in vacuum and in aqueous solution. Electronic structures of acetylcholine were calculated by ab initio quantum mechanical calculations. Three conformations obtained from crystal structures and two from previous calculations were used as starting geometries in the simulations. The trans, gauche conformer had lowest energy both in vacuum … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

1992
1992
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 27 publications
0
10
0
Order By: Relevance
“…The conformations of AcCh and the chimera were energy-minimized about the probable conformation of AcCh bound to the transporter that was determined by . This trans-trans conformer for AcCh is observed during molecular dynamics in water, indicating that it indeed is relatively stable (Edvardsen & Dahl, 1991). The resulting energy-minimized structures are superimposed in Figure 7.…”
Section: Discussionmentioning
confidence: 88%
“…The conformations of AcCh and the chimera were energy-minimized about the probable conformation of AcCh bound to the transporter that was determined by . This trans-trans conformer for AcCh is observed during molecular dynamics in water, indicating that it indeed is relatively stable (Edvardsen & Dahl, 1991). The resulting energy-minimized structures are superimposed in Figure 7.…”
Section: Discussionmentioning
confidence: 88%
“…1(e) is acetylcholine fluoride and Table 1 includes complexes possessing a plane of symmetry and a trans,trans conformation about the two C-O and C-C dihedral arrangements for the central -O-CH 2 -CH 2 -molecular backbone. Here other conformations have been described and reviewed, 1,2 Properties of different conformers will be considered in Section 4 of the present paper.…”
Section: Discussionmentioning
confidence: 99%
“…One group of such fragments are the ATA's (alkyltrimethylammonium compounds) of which an important example is acetylcholine. This has been the subject of molecular dynamics and ab initio studies in relation to its neurotransmitter properties by Edvardsen and Dahl 1 and for which a deficiency in the brain is associated with Alzheimer's disease. These authors concluded that both trans,trans and trans,gauche conformers for the respective central backbone C-O and C-C bonds were present in the free state and in aqueous solution with the trans,gauche form having the lowest energy.…”
Section: Introductionmentioning
confidence: 99%
“…The five ACh + conformers (tg * g, tgg, ttg, tgt, and ttt) are in the low-level group (Figure 3a-e), and the other two conformers (ctg and ctt) are in the high-level group (Figure 3f,g). Other computational studies [20,23,39,40] also conclude the stability of the five low-level conformers. It is important to note that our results support the experiments that observed ACh + (tg * g), (tgg), and (ttg) in their stable states [29,41,42].…”
Section: Thermochemistry Calculationsmentioning
confidence: 90%